Aspek Hak Kekayaan Intelektual Dalam Hukum Perdata: Perlindungan Terhadap Karya-Karya Seni Dan Inovasi Teknologi - Yogi Saputra; Pasha Aizani (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This journal article discusses intellectual property in civil law regarding the protection of art and technological innovation. The main objective is to explore civil law regulations related to the protection of intellectual property in technology innovation and analyze how the implementation of civil law supports the creation and development of art. The research method employs normative juridical research on issues related to intellectual property in art and technological innovation. The findings reveal that civil law regulations governing intellectual property in Indonesia are found in Copyright Law No. 28 of 2014 and Patent Law No. 13 of 2016. Copyright Law protects copyrights, including computer programs, while Patent Law grants exclusive rights to technological innovations. The implementation of civil law, especially copyright, supports artistic creation by providing exclusive rights to creators, creating a legal foundation for artistic control, and fostering economic and creative incentives.